Propaganda and Counter Propaganda in the Digital Society: Institutionalisation 2.0? - Rushchenko, Ihor (Ukrainian Sociological Journal, 2021)
The article highlights the trend of reinstitutionalisation of propaganda and counter propaganda after a brief historical era of international hiatus in the 1990s when the propaganda-related institutions were dismantled in many countries worldwide. The latter trend is exemplified by a number of processes, including the phenomenon of the Russian propaganda that has evolved after Putin took office, and the emergence of the strategic communications offices in Europe starting from 2015. The revival of propaganda 2.0 is a result of the hybrid wars that have engulfed leading countries worldwide. Propaganda is a systematic effort to manipulate other people’s beliefs and spread chaos. Although the current propaganda aims resemble the ones used during the Cold War, the new tech abilities have enhanced its tactics. While the Internet, digitalization and social media platforms offer new opportunities for secret services and relevant experts, the phenomenon of “open consсiousness” allows an average consumer to be unwillingly affected by the messages that contain propaganda. It is argued that counter-propaganda tools should factor in media literacy efforts and building resilience among the general population to withstand disinformation messages. A number of organizations focused at countering propaganda has been created as a means of an institutional solution. Following a watershed moment in Ukraine two relevant organizations were established in 2021: Centre for Countering Disinformation (as part of the National Security and Defense Council) and Centre of Strategic Communications and Information Security (as part of the Ministry of Culture and Information Politics). These organizations aim at carrying out relevant work in line with their EU counterparts.